Three-Component Reaction of Tautomeric Amidines with 3-Ferrocenylmethylidene-2,4-pentanedione. Formation of Polymeric Coordination Complexes of Potassium Ferrocenyl-(hexahydro)pyrimidoxides - Elena I. Klimova; Marcos Flores-Alamo; Tatiana Klimova; Sandra Cortez Maya; Irina P. Beletskaya (Molecules, 2013)
Acetamidine hydrochloride and p-aminobenzamidine dihydrochloride interact with 3-ferrocenylmethylidene-2,4-pentanedione at 80–82 °C in the presence of K2CO3 in the water–alcohol medium in two tautomeric forms (the amidoimine and enediamine ones) with formation of mixtures of pyrimidine and piperidone derivatives and polymeric coordination complexes of potassium ferrocenyl(hexahydro)pyrimidoxides. The structure of the resultant compounds is elucidated on the basis of IR, 1H- and 13C-NMR spectroscopy, mass spectrometry and elemental analysis data. The crystal structures of 6-ferrocenyl-4-hydroxy-4-methyl-2-piperidone, potassium 6-ferrocenyl-4-methyl-2-methylidene(hexahydro)pyrimidin-4-oxide and 2-(4-aminophenyl)-4-ferrocenyl-6-methyl-pyrimidine were determined by X-ray analysis of suitable single crystals.